The structure and function of the eggshell of the leatherback turtle (dermoclzelys coriacea) from Malaysia, with notes on attached fungal forms - Chan, Eng Heng; Solomon, Sally E. (1989)
The structure of the eggshell of the leatherback turtle, Dermocheleys coriacea. conforms generally to that described for contemporary chelonians (Hirsch 1983;' Solomon and Watt 1985;8 Solomon and Tippett 198?9). It is composed of an inner organic membrane and an outer inorganic or mineral layer of calcium carbonate deposited as aragonite. The latter occurs on the organic membrane in discrete units composed of spicules radiating from a central core. In addition to the aragonite crystals, the calcium carbonate can also be deposited as calcite which may assume a variety of shapes variously described as 'blocks, tabular crystals. or flattened lozengeshaped crystals occurring either singly or stacked' (Solomon and Watt 1985).8 The latter also reported the absence of an external cuticular layer which is known to be organic in nature and present in other chelonian eggshells (Hirsch 1983;4 Packard et al. 19845). Phosphorus, present in the eggshells of other sea turtles was not detected in leatherback eggshells (Solomon and Watt 1985).8 In view of the above differences. a further study was conducted" on leatherback eggshells from a different locale-Rantau Abang, Malaysia.